2002
DOI: 10.1002/rcm.625
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography/electrospray ionisation mass spectrometric investigations of imidazoline corrosion inhibitors in crude oils

Abstract: The so-called imidazolines (2-alkyl-1-[ethylalkylamide]-2-imidazolines and 2-alkyl-1-ethylamine-2-imidazolines) are a group of surface-active compounds, complex mixtures of which are used by various industries as surfactants and corrosion inhibitors. Although their industrial synthesis was reported over 100 years ago, few methods for the determination of individual imidazolines in mixtures, including industrial matrices such as crude oils, have been reported. Here we demonstrate that spiking of crude oils with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Fatty acids that have been reported in produced water range from C 1 to C 9 , and reported concentrations are also shown in Table 1. Although there are methods for measuring production additives, [8][9][10][11] little data is available about specific compounds and concentrations of corrosion and scale inhibitors, demulsifiers and defoamers, and biocides in produced water. Thus, engineering treatment methods to remove these components can only be done in collaboration with industrial partners.…”
Section: Composition Of Produced Watersmentioning
confidence: 99%
“…Fatty acids that have been reported in produced water range from C 1 to C 9 , and reported concentrations are also shown in Table 1. Although there are methods for measuring production additives, [8][9][10][11] little data is available about specific compounds and concentrations of corrosion and scale inhibitors, demulsifiers and defoamers, and biocides in produced water. Thus, engineering treatment methods to remove these components can only be done in collaboration with industrial partners.…”
Section: Composition Of Produced Watersmentioning
confidence: 99%
“…Using these equations, the (MRD) 2 and refractive index of compounds in 0.1 M solutions were calculated and are given in Table 3. It is observed that both (MRD) 2 and refractive index of compounds are different in each solvent. This again proves that in different solvents, intermolecular interactions are different which affects these parameters.…”
Section: Density and Refractiove Indexmentioning
confidence: 99%
“…The synthesis of imidazoline derivatives continues to attract much interest in organic chemistry due to its various therapeutic properties [1][2][3][4][5][6][7][8]. This class of compounds is known to have applications in various fields [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In CE, amines are generally separated as cationic species, and detected indirectly using low-pH electrolyte systems containing UV-absorbing additives [29 -34]. Sophisticated techniques, such as liquid chromatography/electrospray ionisation multistage mass spectrometry [35] and particle induced X-Ray emission spectroscopy [36], were applied as well. Different components of the corrosion inhibitor can be analytically determined; ester peak was used to quantify the concentration of the residual inhibitor in inhibitor/diesel solution by using carbon-13 NMR and Fourier Transform infrared spectroscopy [37].…”
Section: Introductionmentioning
confidence: 99%